STUDY ON DEPOSITIONAL ENVIRONMENT IN ‘Z’ FIELD BASED ON LOG MOTIFS CHARCTERISTICS AND ITS LINK WITH THE ELASTIC PROPERTIES - MURUTHY, SAMINI PANDIAN (Universiti Teknologi PETRONAS, 2015)
This dissertation emphasizes on the link between log motif characteristics and elastic properties of a tertiary reservoir in Malay basin. Petrophysical well log and elastic properties were integrated in an analysis of the reservoir characteristics of Z field, from Malay basin to enhance the prediction of depositional environment. This work highlights the analysis which started with lithology identification where it was built up from well logs consideration that the study range is portrayed by sand-shale interbedding showing the brief of log motifs and several parasequences stacked inside of the fundamental sequence. The scope of this research is to utilize the well logs to have a quick evaluation on the reservoir of interest’s depositional environment by also involving the elastic properties of the rocks. This method concentrates on the lateral change in content of fluid as it aides to assume the lateral continuity or extent of the reservoir when seismic data is not accessible. Despite the sediment packages, the fluid content will also be identified in the reservoirs on the basis of neutron/density log signatures to enhance the level of confidence of the fluid distribution with the elastic property analysis. Just a solitary technique is not generally enough to anticipate the reservoir properties and could prompt vagueness, thus by integrating diverse techniques and methods the vagueness could be minimized. Moreover, understanding the depositional environment of any reservoirs might enhance the interpretation which give us better comprehension of reservoir information that can't undoubtedly picked up by conventional methods. Consequently, the key contribution of this dissertation is to improve the prediction of Depositional environment of the field by integrating petrophysical well log and elastic properties of the reservoir.